Motivational Mechanisms and Outcome Expectancies Underlying the Approach Bias toward Addictive Substances - Watson, Poppy; De Wit, Sanne; Hommel, Bernhard; Wiers, Reinout W. (Frontiers in Psychology, 2012)
Human behavior can be paradoxical, in that actions can be initiated that are seemingly incongruent with an individual’s explicit desires. This is most commonly observed in drug addiction, where maladaptive behavior (i.e. drug seeking) appears to be compulsive, continuing at great personal cost. Approach biases towards addictive substances have been correlated with actual drug-use in a number of studies, suggesting that this measure can, in some cases, index everyday maladaptive tendencies. At present it is unclear whether this bias to drug cues is a Pavlovian conditioned approach response, a habitual response, the result of a Pavlovian-instrumental transfer process or a goal-directed action in the sense that expectancy of the rewarding effects of drugs controls approach. We consider this question by combining the theoretical framework of associative learning with the available evidence from approach bias research. Although research investigating the relative contributions of these mechanisms to the approach bias is to date relatively limited, we review existing studies and also outline avenues for future research.